Microplastic contamination in Czech drinking water: insights from comprehensive monitoring - Jan Halfar; Silvie Heviánková; Kateřina Brožová; Kristina Čabanová; Alice Valigůrová; Oldřich Motyka (Environmental Sciences Europe, 2024)
Abstract The growth of global plastic production and the associated increase in microplastic pollution in the environment has attracted increasing attention from both scientists and the general public. Drinking water from public water supply systems is essential for human life and therefore ensuring its high quality is a priority. The aim of this study was to detect and identify microplastics in drinking water from public water supply systems. Water samples were collected from various locations across the Czech Republic during two sampling campaigns in 2021 and 2023. A total of 58 samples and 580 particles were analyzed using μ-FTIR (micro-Fourier-transform infrared spectroscopy). These particles were categorized by material, shape, color, and quantity. Of the analyzed particles, 196 were identified as microplastics. Except for one sample, where no microplastics were detected, the concentration ranged from 20 to 180 microplastics per liter during the first campaign and from 20 to 120 microplastics per liter in the second campaign. In the first campaign, fibers and transparent microplastics were predominantly detected, while in the second collection, fragments and blue microplastics were more common. The most frequently observed materials were paper with polyethylene coating, polyethylene terephthalate (PET), and polyester (PES). This study also provides data on the average daily intake of microplastics via drinking water, calculated as 2 and 2.1 MP/kg/day, with all results undergoing statistical evaluation. Furthermore, the study addresses new European legislation and the proposed standardized methodology, which represents a significant step toward achieving consistent results across studies and, upon its adoption, will likely influence the direction of research on microplastics in drinking water. However, as discussed in the study, the methodology contains several problematic aspects, which are elaborated upon. With the planned inclusion of microplastics on the EU list of substances to be monitored, it is essential to continue research and collect more data. This study confirms the presence of microplastics and provides detailed information on their characteristics in drinking water supplied by public water systems in the Czech Republic. Highlights Two drinking water sampling campaigns were carried out. Microplastics were found in 57 out of 58 analyzed drinking water samples. The average MP concentrations in two campaigns amounted 68.3 and 65 MP/L. Material, shape, and color of all detected microplastics were identified. Average daily MP intake via drinking water was calculated as 2 and 2.1 MP/kg/day. Graphical abstract